SENAM KAKI DAN STIMULASI KUTANEUS DENGAN VCO MENINGKATKAN KELEMBABAN KULIT KAKI PADA DIABETISI DI PUSKESMAS SUKAWATI I KABUPATEN GIANYAR - I Wayan Sukawana; I Made Sukarja; Ni Made Wedri (Poltekkes Kemenkes Denpasar, 2020)
Abstract Autonomic neuropathy in diabetes mellitus impact the feet to losing their natural ability to moisturize the overlying skin, so that the skin of the feet becomes dry, cracked, and prone to infections (ulcers). This activity aims to enable people with diabetes to be able to do foot exercises and cutaneous stimulation with VCO so that the skin moisture in their feet increases. Foot skin moisture was measured by a Skin Moisture Analyzer at ten right foot points before and after four weeks of diabetes people doing foot exercises and cutaneous stimulation with VCO. Average foot moisture before foot exercises and cutaneous stimulation with VCO of 38.93 then increased to 49.55. Paired t test proved that there was a significant increase in foot skin moisture after activity (t = -4.66 and significance value = 0.00). All people with diabetes are advised to continue their activities.Key words: Skin Moisture, Foot Exercises, Cutaneous Stimulation